A study of user satisfaction and net benefits in Indonesia through the DeLone and McLean Model for E-Government success - Rahmatullah, Rahmatullah; Habibi, Akhmad; Khaeruddin, Khaeruddin; Yaqin, Lalu Nurul; Alharmali, Turki Mesfer; Fauzee, Mohd Sofian Omar; Mahat, Jazihan (Springer Nature, 2025)
The current research examines the success of e-government systems by utilizing success-based techniques of information systems (IS) from the viewpoint of government personnel. Nine hypotheses were included to test the relationships among variables (information quality, service quality, system quality, behavioral intention, user satisfaction, and net benefits). The data acquired from 232 employees using e-government systems in Indonesia was analyzed using structural equation modeling (SEM) techniques. This study was a practical assessment of a model used to measure the effectiveness of e-government systems. The model used elements from the revised DeLone and McLean IS success model. Statistical analysis shows that seven out of nine hypothesized correlations between the seven success variables are statistically significant. The strongest correlation emerged between behavioral intention and net benefits, while the weakest correlation was between system quality and behavioral intention. The findings highlight the importance of intention and net benefits that can be utilized to evaluate the effectiveness of e-government systems in the context of developing countries, which are practical for SDG 16—Peace, Justice, and Strong Institutions. To better understand e-government user satisfaction, future studies should test the model in broader geographic contexts, especially in developing countries like Indonesia.